Development of captive Juvenile male Grasscutters (Thryonomys swinderianus. Temminck 1827) fed with two common forage grass species in Nigeria (Journal of Bio-Science, 2015)
Context: Sustainable utilization of abundant forage grass species in Nigeria is very crucial in grasscutter domestication programme. Objective: This study evaluates comparative effects of Elephant grass (Pennisetum purpureum) and Gamba grass (Andropogon gayanus) parts on growth performance of captive-bred juvenile male grasscutters. Materials and Methods: The study was conducted inside Grasscutter Domestication Unit of Federal College of Wildlife Management, New Bussa, Niger State, Nigeria. The experimental animal comprised of twenty-four juvenile males (JM) with mean live-weight of 410±2.11g fed four basal dietary treatment combinations: Elephant grass stem (EGS), Elephant Grass Leaf (EGL), Gamba Grass Stem (GGS) and Gamba Grass Leaf (GGL) in a 2 x 2 factorial arrangement for 120 days to obtain data which includes feed intake (FI), feed conversion ratio (FCR), weight gain (WG), nutrient digestibilities of dry matter (DM) and crude fibre (CF). Results: Average daily feed intake (FI) in JM was significantly (p